Effect of an aluminum chloride hemostatic agent on the dentin shear bond strength of a universal adhesive - Sujin Kim; Yoorina Choi; Sujung Park (Restorative Dentistry & Endodontics, 2023)
ObjectivesThis study investigated the effect of an aluminum chloride hemostatic agent on the shear bond strength (SBS) of a universal adhesive to dentin.Materials and MethodsEighty extracted human molars were trimmed at the occlusal dentin surfaces and divided mesiodistally. According to hemostatic agent application, specimens were randomly allocated into control (C) and hemostatic agent (Traxodent; H) groups. Each group was divided into 4 subgroups according to the adhesive system (n = 20): Scotchbond Multi-Purpose (SBER), Clearfil SE Bond (CLSE), All-Bond Universal etch-and-rinse mode (ALER), and All-Bond Universal self-etch mode (ALSE). SBS was measured for half of the specimens at 24 hours, and the other half were thermocycled in water baths (group T). Fracture surfaces were examined to determine the failure mode. The SBS was measured, and data were analyzed using 1-way analysis of variance, the Student’s t-test, and the Tukey honestly significant difference test (p = 0.05).ResultsNo significant differences in SBS were found between groups C and H for any adhesive system at 24 hours. After thermocycling, a statistically significant difference was observed between CT+ALSE and HT+ALSE (p < 0.05). When All-Bond Universal was applied to hemostatic agent-contaminated dentin, the SBS of H+ALSE was significantly lower than that of H+ALER (p < 0.05). The SBER subgroups showed no significant differences in SBS regardless of treatment and thermocycling.ConclusionsWhen exposed dentin was contaminated by an aluminum chloride hemostatic agent before dentin adhesive treatment, application of All-Bond Universal in etch-and-rinse mode was superior to self-etch mode.